2021
DOI: 10.14740/gr1404
|View full text |Cite
|
Sign up to set email alerts
|

Is the Use of Proton Pump Inhibitors a Predisposing Factor for Pyogenic Liver Abscesses?

Abstract: Background: Proton pump inhibitors (PPIs) increase gastric pH by reducing acid production. The resulting alkaline milieu in the stomach increases the risk of bacterial translocation. This study aimed to investigate if there is a correlation between PPI use and developing pyogenic liver abscesses. Methods:In this retrospective case-control analysis, we studied adult patients diagnosed with cryptogenic liver abscess at Northwell hospitals between 2015 and 2019. Adult patients with the diagnosis of liver abscess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…We suspected that prolonged intestinal pseudo-obstruction led to bacterial growth in the intestinal tract and caused bacterial seeding into the enterohepatic circulation via the portal venous system, eventually resulting in a liver abscess. In addition, Elfiky et al 14 recently reported that patients using PPIs are associated with 2.36 times increased risk of developing liver abscess because PPIs elevate the gastric pH, thus increasing the risk of bacterial translocation. Our patient had been prescribed a PPI, namely, lansoprazole, for more than a year.…”
Section: Discussionmentioning
confidence: 99%
“…We suspected that prolonged intestinal pseudo-obstruction led to bacterial growth in the intestinal tract and caused bacterial seeding into the enterohepatic circulation via the portal venous system, eventually resulting in a liver abscess. In addition, Elfiky et al 14 recently reported that patients using PPIs are associated with 2.36 times increased risk of developing liver abscess because PPIs elevate the gastric pH, thus increasing the risk of bacterial translocation. Our patient had been prescribed a PPI, namely, lansoprazole, for more than a year.…”
Section: Discussionmentioning
confidence: 99%
“…143 In a recent case-control study, PPI use similarly increased the risk of septic liver abscess (aOR 2.27, 95% CI 1.55-3.32). 141 PPIs also appeared to lead to a worse prognosis for liver abscess. 16 PPIs were associated with increased index mortality in individuals with liver abscess, and after adjusted for confounding factors, PPIs remained an independent predictor (adjusted OR 2.56, 95% CI 1.01-6.46).…”
Section: Ppi and Liver Abscessmentioning
confidence: 98%
“…Another study not only found that PPIs were responsible for an increased risk of liver abscess, but also revealed that there was a dose–response relationship, as PPIs accumulated within 90 days of PPI initiation 143 . In a recent case–control study, PPI use similarly increased the risk of septic liver abscess (aOR 2.27, 95% CI 1.55–3.32) 141 . PPIs also appeared to lead to a worse prognosis for liver abscess 16 .…”
Section: Ppi and Liver Abscessmentioning
confidence: 99%
See 1 more Smart Citation